Interactive creation of digital derivatives thematic maps of the base layer «soil» of the land information systems of the Republic of Belarus - Klebanovich, Nikolai V.; Prokopovich, Sergey N.; Sazonov, Aliaksei A. (Journal of the Belarusian State University. Geography and Geology, 2017)
The article discusses the possibility of interactive automated creation the thematic maps of the base layer «soil» of the land information systems of the Republic of Belarus. The authors proposed a processing module of thematic information Soil Analyst created in the environment of ArcGIS for Desktop 10.3. Performed spatial and thematic GIS-analysis created lithology maps, maps of parent rocks, cartograms of physical clay content, maps of soils means to reclamation, soil maps in the international classification WRB system. Created by the authors digital thematic maps on a completely new organizational and spatial level determine the soil cover of the research area based on a joint analysis of large groups of parameters (parameters of the relief, the genesis and nature of the pedogenesis, the degree of humidification, size distribution of the soil, morphometric characteristics, the correlation characteristics of the classifications is interconnected, which is very important for the complete characterization of a soil as a whole, and the individual components of the landscape in particular.
Keywords: digital soil mapping; thematic maps; land information systems; geodatabases; GIS analysis